Udaya Parwata's Innovative Music | Musik Inovatif Udaya Parwata - Putra, I Wayan Gede Rikiana Adi; -, Wardizal (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
This article explains the process of creating music entitled Udaya Parwata to describe the beauty of Mount Agung, which is the highest volcano on the island of Bali. Mount Agung has an essential role in the lives of the surrounding community. The close relationship between Mount Agung and the diversity of Karangasem's traditional arts reflects the harmonious balance between humans and nature. The innovative musical artwork